Application of numerical simulation for lightweight design / Marcel Graf ... [et al.] - Graf, Marcel; Härtel, Sebastian; Awiszus, Birgit (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Due to the increasing lightweight construction efforts to reduce component weight and thus minimize the energy demand for mobilisation of moving masses, light metals or even plastic applications are growing in importance. In order to realise the process development with consideration of the material, its behaviour must be known. This paper aims to show the importance of numerical process design and how it can be validated with experiments. For the thermo-mechanical simulation to generate results with high accuracy, the use of real material data is necessary. Depending on the investigated process, different characterisation possibilities are available. Here, the compression test was carried out, for example, to determine the forming behaviour of aluminium (EN AW-6060) and magnesium alloys (AZ31) and for a polyamide without and with glass fibre reinforced (PA 6 and PA6-GF30) on elevated temperatures and strain rates of hot bulk forming processes. In this case, the sample position, especially in the case of the polyamide, received increased attention. Thus, it was found that glass fibre reinforced plastics (PA-GF30) can be compressed differently in the longitudinal direction than perpendicular to the extrusion direction. Furthermore, an enhancement of the forming limit and a reduction of the forming force with increasing temperature could be observed for all investigated materials. In addition to the forming behaviour, the thermo-dynamic material properties are at least just as important for the purposed thermo-mechanical process simulations. These were also determined by experimental simulation for the analysed materials in order to regard the internal microstructure. Then, the implementation of all these material data into the FE software simufact.forming V15 and MSC Marc/Mentat was carried out in order to predict a forging process as well as an additive manufacturing process for the semi-finished products. Finally, the calibration of the FE models took place to verify their accuracy. This is the first study undertaken to characterise the forming behaviour of plastics and to study the production of layered magnesium components for further forming processes.